1989
DOI: 10.1113/jphysiol.1989.sp017828
|View full text |Cite
|
Sign up to set email alerts
|

GABA and glycine channels in isolated ganglion cells from the goldfish retina.

Abstract: SUMMARY1. Adult goldfish retinas were enzymatically dissociated and ganglion cells were maintained in culture for periods of 1-5 days. Ganglion cells could be identified by their morphology, and this identification was confirmed by retrograde transport of the fluorescent dye Fast Blue injected into the optic nerve stub.2. All the ganglion cells tested responded to 30 ,tM-GABA or 100 /IM-glycine between 2 and 30 h after enzymatic dissociation of the retina.3. Whole-cell responses to 30 jM-GABA or glycine declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 39 publications
6
22
0
Order By: Relevance
“…GLY (100-200 pM) produced inward, desensitizing currents in every parasol and midget cell tested at a holding potential of -70 mV. The pharmacology and ionic selectivity of GLY receptors on midget and parasol cells were similar to those reported in other retinal neurons (31)(32)(33)(34). For example, strychnine (2-4 ,uM) reversibly blocked the responses to 100 pM GLY by 68% ± 16% (mean ± SD, n = 5) (Fig.…”
Section: Identification Of Midget and Parasol Cells In Primate Retinalsupporting
confidence: 71%
“…GLY (100-200 pM) produced inward, desensitizing currents in every parasol and midget cell tested at a holding potential of -70 mV. The pharmacology and ionic selectivity of GLY receptors on midget and parasol cells were similar to those reported in other retinal neurons (31)(32)(33)(34). For example, strychnine (2-4 ,uM) reversibly blocked the responses to 100 pM GLY by 68% ± 16% (mean ± SD, n = 5) (Fig.…”
Section: Identification Of Midget and Parasol Cells In Primate Retinalsupporting
confidence: 71%
“…It is likely that retinal neurons express glycine receptors containing ␤ subunits. The main conductance of glycine channels in goldfish ganglion cells is ϳ16 pS (Cohen et al 1989), far below the ϳ80 pS expected in GlyRs made exclusively from alpha subunits. The presence of ␤ subunits makes the potency of picrotoxinin in retina, relative to alpha homomeric receptors, even more unexpected (Pribilla et al 1992).…”
Section: Comparison Of Antagonists In Native and Heterologously Exprementioning
confidence: 74%
“…Yet many studies have shown that picrotoxin is not particularly selective and may act to block glycine receptors (Pribilla et al 1992;Shan et al 2001). There are also reports that SR95531 and bicuculline can inhibit glycine receptors (Cohen et al 1989;Dieudonne 1995;Sun and Machu 2000). We therefore wanted to test these antagonists at commonly employed concentrations to determine their utility in separating GABA and glycine neural circuits in retina.…”
Section: Introductionmentioning
confidence: 99%
“…To increase the likelihood of a thorough space clamp and dialysis of the cytoplasm against the patch electrode solution (see below), cells were used only if they were neurite-free-namely, usually within 12 hr after cells were dissociated (16). All recordings described here are from somata identified as those of ganglion cells by morphological criteria (5,7).…”
Section: Methodsmentioning
confidence: 99%